Development in Eastern Europe and the South Caucasus Armenia, Azerbaijan, Georgia, Republic of Moldova and Ukraine. (OECD, Development Centre, 2011)
The economic crisis, the second economic shock to hit the Eastern Europe and the South Caucasus region after the collapse of the Soviet Union, has been a warning and a call to action. The region has many advantages and much potential, but some of this was squandered during the boom years of the 2000s. The studies contained in this volume demonstrate that the potential is still there and that the measures that need to be taken to realize that potential are feasible and affordable. Some of them can have an almost immediate effect, such as easing access to finance for small and medium-sized enterprises and opening up new markets for the region's goods. Others are more medium-term, such as redeveloping product lines in the steel industry or in agriculture. Some of the most critical reforms, like raising the level of education and improving health care, will require political and economic investment over the long term.--Publisher's description.